Riparian restoration benefits across space and time in subtropical Australia: From drinking water quality to wider society - Joseph M. McMahon; James C.R. Smart; Ben Stewart-Koster; Syezlin Hasan; James S. Shortle; William N. Venables; Andrew Smolders; Morag Stewart; Don Butler; Jon M. Olley; David P. Hamilton; Stuart Bunn (Ecosystem Services, 2026)

Chilling Consequences: Recruitment Failure of Four Native Fish Species in a Thermally Polluted, Regulated River - Laura E. Michie; James N. Hitchcock; Simon M. Mitrovic; Matthew Gordos; Gavin L. Butler (Fisheries Management and Ecology, 2026)
Cold water pollution (CWP), caused by the release of unseasonably cool water from the bottom of large reservoirs to downstream rivers, is an escalating global threat to riverine biodiversity that is exacerbated by future dam developments and climate change. This study examined the impact of CWP on native fish populations in the Severn River (NSW, Australia), downstream of a large reservoir. Long‐term data (2012–2024) revealed chronic CWP, with thermal regimes frequently below thresholds required for native fish spawning during the austral summer period. An aged population structure and chronic recruitment failure were evident in four native fish species. Additionally, native fish stocking efforts have resulted in limited success. We recommend both long‐term CWP mitigation and immediate adaptive management strategies, such as optimising stocking practices and opportunistic water management actions, as critical to sustaining native fish populations.

Viability of seed balls for large-scale restoration of native plant communities in New Zealand - James W. Griffiths; Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; Jennifer Alderton-Moss; Karin van der Walt; Anja McDonald; Kirsty Moran (New Zealand Journal of Botany, 2025)

Physical properties of seed ball formulations - Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; James W. Griffiths (New Zealand Journal of Botany, 2025)

Cryptic foreland basin strata of the southeastern Trans-Hudson Orogen revealed by detrital zircon geochronology - Jared P. Butler; Alana M. Hinchey; James L. Crowley (Precambrian Research, 2025)

Sequential model-based design of experiments for a heat-integrated biomass downdraft gasifier - Houda M. Haidar; James W. Butler; Peter Gogolek; Kimberley B. McAuley (Bioresource Technology, 2025)

Performance of summary measures of core body temperature in heat-related health outcome regression models - M. Dally; A. Dye-Robinson; Y. Li; D. Jaramillo; K. Villarreal-Hernandez; L. Krisher; J. Butler-Dawson; J. Schaeffer; J. L. Adgate; K. A. James; L. S. Newman (International Journal of Biometeorology, 2025)

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Modeling of a heat-integrated biomass downdraft gasifier: Influence of feed moisture and air flow - Houda M. Haidar; James W. Butler; Samira Lotfi; Anh-Duong Dieu Vo; Peter Gogolek; Kimberley McAuley (Biomass and Bioenergy, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

Adaptation pathways to inform policy and practice in the context of development - Edward Sparkes; Edmond Totin; Saskia E. Werners; Russell M. Wise; James R.A. Butler; Katharine Vincent (Environmental Science & Policy, 2023)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Correction to: Development of Decisional Values Statements for Lung Cancer Screening among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

Development of Decisional Values Statements for Lung Cancer Screening Among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

The multi-element stoichiometry of wet eucalypt forest is transformed by recent, frequent fire - Orpheus M. Butler; James J. Elser; Tom Lewis; Sarah C. Maunsell; Mehran Rezaei Rashti; Chengrong Chen (Plant and Soil, 2020)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

The stoichiometric legacy of fire regime regulates the roles of micro‐organisms and invertebrates in decomposition - Orpheus M. Butler; Tom Lewis; Mehran Rezaei Rashti; Sarah C. Maunsell; James J. Elser; Chengrong Chen (Ecology, 2019)
Decadal‐scale increases in fire frequency have the potential to deplete ecosystems of essential nutrients and consequently impede nutrient‐limited biological processes via stoichiometric imbalance. Decomposition, a fundamental ecosystem function and strong driver of future fire occurrence, is highly sensitive to nutrient availability and is, therefore, particularly important in this context. Here we show that 40 yr of quadrennial (4yB) and biennial (2yB) prescribed burning result in severely P‐ and N‐depleted litter stoichiometry, respectively, relative to fire exclusion. These effects exacerbated the nutrient limitation of microbial activities, constraining litter decomposition by 42.1% (4yB) and 23.6% (2yB) relative to unburned areas. However, invertebrate‐driven decomposition largely compensated for the diminished capacity of micro‐organisms under 4yB, suggesting that invertebrates could have an important stabilizing influence in fire‐affected ecosystems. This effect was strongly positively coupled with the strength of microbial P‐limitation and was not obviously or directly driven by fire regime‐induced changes in invertebrate community assemblage. Together, our results reveal that high‐frequency fire regimes promote nutrient‐poor, carbon‐rich ecosystem stoichiometry and, in doing so, disrupt ecosystem processes and modify the relative functionality of micro‐organisms and invertebrates.

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

High-frequency fire alters soil and plant chemistry but does not lead to nitrogen-limited growth of Eucalyptus pilularis seedlings - Orpheus M. Butler; Mehran Rezaei Rashti; Tom Lewis; James J. Elser; Chengrong Chen (Plant and Soil, 2018)

The phosphorus‐rich signature of fire in the soil–plant system: a global meta‐analysis - Orpheus M. Butler; James J. Elser; Tom Lewis; Brendan Mackey; Chengrong Chen (Ecology Letters, 2018)
The biogeochemical and stoichiometric signature of vegetation fire may influence post‐fire ecosystem characteristics and the evolution of plant ‘fire traits’. Phosphorus (P), a potentially limiting nutrient in many fire‐prone environments, might be particularly important in this context; however, the effects of fire on P cycling often vary widely. We conducted a global‐scale meta‐analysis using data from 174 soil studies and 39 litter studies, and found that fire led to significantly higher concentrations of soil mineral P as well as significantly lower soil and litter carbon:P and nitrogen:P ratios. These results demonstrate that fire has a P‐rich signature in the soil–plant system that varies with vegetation type. Further, they suggest that burning can ease P limitation and decouple the biogeochemical cycling of P, carbon and nitrogen. These effects resemble a transient reversion to an earlier stage of ecosystem development, and likely underpin at least some of fire's impacts on ecosystems and organisms.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation - James R. Butler; Gregory R. Martens; Jose L. Estrada; Luz M. Reyes; Joseph M. Ladowski; Cesare Galli; Andrea Perota; Conor M. Cunningham; Matthew Tector; A. Joseph Tector (Transgenic Research, 2016)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)

Conservation Genetics of North American Freshwater Mussels Amblema and Megalonaias - Margaret Mulvey; Charles Lydeard; Debra L. Pyer; Kimberly M. Hicks; Jayne Brim‐Box; James D. Williams; Robert S. Butler (Conservation Biology, 1997)
Freshwater bivalves are among the most endangered groups of organisms in North America. Efforts to protect the declining mussel fauna are confounded by ambiguities associated with recognition of distinct evolutionary entities or species. This, in part, is due to the paucity of reliable morphological characters for differentiating taxa. We have employed allozymes and DNA sequence data to search for diagnosably distinct evolutionary entities within two problematic genera of unionid mussels, Amblema and Megalonaias. Within the genus Amblema three species are recognized based on our DNA sequence data for the mitochondrial 16S rRNA and allozyme data (Amblema neislerii, A. plicata, and A. elliotti). Only one taxonomically distinct entity is recognized within the genus Megalonaias—M. nervosa. Megalonaias boykiniana of the Apalachicolan Region is not diagnosable and does not warrant specific taxonomic status. Interestingly, Megalonaias from west of the Mississippi River, including the Mississippi, exhibited an allozyme and mtDNA haplotype frequency shift suggestive of an east‐west dichotomy. The results of this study eliminate one subspecies of Amblema and increase the range of A. plicata. This should not affect the conservation status of “currently stable” assigned to A. plicata by Williams et al. (1993). The conservation status of A. elliotti needs to be reexamined because its distribution appears to be limited to the Coosa River System in Alabama and Georgia.